PENINGKATAN PEMAHAMAN BAHAYA ROKOK PADA REMAJA DALAM PENGENDALIAN HIPERTENSI - Prihatin, Kurniati; Aswati, Aswati; Ruli Fatmawati, Baiq (Stikes Yarsi Mataram, 2024)
Hypertension is one of the causes of premature death in people around the world. One of the risk factors for hypertension is smoking habits. The long-term effects of smoking are increased blood pressure due to increased inflammatory substances, endothelial dysfunction, plaque formation, and vascular damage. Therefore, this community service aims to increase teenagers' understanding of the dangers of smoking so that they can hopefully be able to control the incidence of hypertension sufferers. This activity was attended by 30 teenagers in Setiling 3 Hamlet, Setiling Village, North Batukliang District, Central Lombok, West Nusa Tenggara using LCD projectors and leaflets as media. The method used is lecture and discussion. This service is able to increase the knowledge and understanding of teenagers regarding the dangers of smoking on health, especially in increasing the risk of hypertension.